Treatment of textile wastewater by thermolysis and coagulation / Roslinda Zulkifli - Zulkifli, Roslinda (Faculty of Applied Sciences, 2010)
The decolorization and reduction of COD of dyeing wastewater from textile mill was conducted using catalytic thermal treatment (thermolysis) accompanied with and without coagulation. Thermolysis in the presence of a homogeneous iron (III) chloride catalyst was found to be effective in comparison to other catalysts FeS0₄, ZnO and CUSO₄ used. A maximum reduction of COD and color achieved are 31% and 94%, respectively, at a catalyst concentration of 0.05 g/L and at pH 10. Commercial alum was the most effective coagulant for coagulation, resulting in 28% COD and 42% color reduction at pH 8 and coagulant dosage of 1.0 mL of 5% solution. Coagulation of the clear supernatant obtained after thermolysis resulted in an overall reduction of 81% COD and 99% color at pH 8 and coagulant dosage of 1.0 mL. The application of thermolysis followed by coagulation, thus, is the most effective treatment method in removing nearly 81% COD and 99% color at a lower dose of coagulant (0.5 g/L).